The design and synthesis of multidentate N-heterocyclic carbenes as metathesis catalyst ligands,Design and synthesis of multidentate NHC as metathesis catalyst ligands - Truscott, Byron John (Rhodes University, Faculty of Science, Department of Chemistry, 2011)
This study has focused on the design and preparation of bi"“ and tridentate N"“Heterocyclic Carbene (NHC) ligands in order to investigate the effect of a multidentate approach to the formation, stability and catalytic activity of coordination complexes. Chapters 1 "“ 3 provide background information of relevant catalysis, carbene and coordination chemistry, followed by previous work performed within our research group. In Chapter 4 attention is given to the synthetic aspects of the research conducted, comprising two distinct approaches to the preparation of unsymmetrical saturated and unsaturated NHCs. Firstly, an investigation of the saturated NHC ligands yielded three novel, unsymmetrical pro"“ligands, viz., two halopropyl imidazolinium salts and a bidentate hydroxypropyl imidazolinium salt. Secondly, eight imidazolium salts have been generated, including a hydroxypropyl analogue and novel decyl and tridentate malonyl derivatives. These compounds were prepared using microwave"“assisted methodology for the alkylation of N"“ mesitylimidazole "“ an approach that drastically reduced reaction times (from 8 hours "“ 7 days to ca. 0.5 "“ 2 hours) and facilitated isolation of the imidazolium salts. Many of the compounds prepared in this study are novel and were fully characterized using HRMS and 1"“ and 2"“D NMR analysis. Coordination studies using a selection of the prepared pro"“ligands afforded an alkoxy"“NHC silver derivative and four novel Ru"“complexes, viz., Grubbs II"“type Ru"“complexes containing:"“ chloropropyl imidazolinylidene; propenyl imidazolylidene; and bidentate alkoxypropyl imidazolylidene ligands. Furthermore, a well"“defined benzyl mesitylimidazolylidene Ru"“complex has been isolated, which exhibited good stability in air. DFT"“level geometry"“optimization studies, using the Accelrys DMol3 package have given valuable insights into the likely geometries of the prepared and putative catalysts.
Keywords: Carbenes (Methylene compounds); Heterocyclic compounds; Ligands; Ligands -- Design; Metathesis (Chemistry); Catalysis